Tradisi Pernikahan dengan Kesetaraan Keturunan dalam Keluarga Para Mas Sidosermo Kecamatan Wonocolo Surabaya Dan Berbek Kecamatan Waru Sidoarjo - Rohmat Hidayatulloh; Arif Jamaluddin Malik (AL-HUKAMA, 2017)
This is a field research which aims to determine: (1) How the equality of marriage within the descendants of family of Mas in Sidosermo, Wonocolo, Surabaya and Berbek, Waru, Sidoarjo; (2) and how the equality of marriage within the descendants of family of Mas in Sidosermo, Wonocolo, Surabaya and Berbek, Waru, Sidoarjo under the Islamic law perspective. Based on the interview, it can be stated that most of the Mas family in Sidosermo, Wonocolo, Surabaya strongly consider the equality of the candidate of husband and wife in terms of family and religion. This, for the Mas family, is a very basic thing to be fulfilled. This is because they believe that they are the descendants of the Messenger of Allah. Unlike in Berbek, the wedding tradition for the Mas in Berbek does not currently take into account of nasab from prospective husband or wife. The most important things are there is a match between bride and groom and they have  a feasible science and a good moral.